Consumer decision-making and legal awareness in the circular economy: A regulatory perspective - Tick, Andrea; Ruso, Jelena; Anton, Sorin Gabriel; Buzdugan, Adriana (Serbian Journal of Management, 2025)
Linear economic models have been regular business since the industrial revolution, but, the deepening sustainability problems and the accumulation of waste gave birth to the concept of circular economy, which might ease the ecological burden on industries and societies. The operation of such economic models is always backed by rules and regulations developed by national and intranational legislative bodies. The aim of the paper is to investigate the consumers' familiarity with circular economy legislation and how this familiarity correlates with sustainable consumption behavior. The main result highlights a positive and significant link between knowledge of circular legislation and its perceived impact on consumer decisions, confirming that legal information can facilitate more sustainable behaviors. Three distinct segments of consumers according to their level of knowledge and attitude have been identified, suggesting that the public is not homogeneous in relation to the circular economy. Our findings have significant practical and policy implications. First, they suggest the need to strengthen large-scale consumer education and information efforts. Second, the normative implications of the study suggest further efforts to adapt the regulatory framework to sustainability objectives, while ensuring that this framework is coherent and harmonized across countries.
Keywords: Circular economy; Ecological footprint labelling; EFA; K-Means clustering; Legal regulations